ملامح الممارسة الأنتروبولوجية الجزائرية - حمادوش, نوال (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
This paperaimsatshedding light upon the personality, identity, methodology and knowledge of the researcher “Tasadit Yassin,” whoisconsidered as one of the prominent modern Amazigh Algerian anthropological figures.